Cutaneous Manifestations of Juvenile Dermatomyositis: A Case Series - Sunanda Arun Mahajan; Jayati Shailesh Dave; Vidya D Kharkar (Wolters Kluwer Medknow Publications, 2021)
Juvenile Dermatomyositis (JDM) is an idiopathic inflammatory myopathy characterized by the weakness of skeletal muscle and pathognomonic skin rashes. Studies focusing on the cutaneous manifestations of JDM are sparse. The objectives of the study were (1) to describe cutaneous changes seen in JDM and (2) to observe nailfold capillaroscopy (NFC) changes in patients with JDM. This was a retrospective case series. All children under the age of 15 years who were diagnosed to have dermatomyositis according to the Bohan and Peter criteria and on histopathology presenting to the dermatology outpatient department during a period of 1.5 years (January 2017-June 2018) were included in the series. Details including clinical features and finding from investigations such as NFC, muscle magnetic resonance imaging, electromyography, muscle enzymes, and biopsy were noted. Statistical analysis was performed on the basis of measures such as percentage and frequency of cutaneous manifestations. A total of eight cases of JDM were included, with average age at presentation being 7.62 years. Among the cutaneous manifestations, the most common presenting features were heliotrope rash and Gottron's papule. Facial telangiectasias, calcinosis cutis, and hypertrichosis were seen in 37.5% of cases. Other cutaneous features seen were confluent and reticulate violaceous erythema, cutaneous ulcer, and periungual telangiectasia with cuticular overgrowth. NFC was suggestive of scleroderma-dermatomyositis pattern in all six patients in whom it was conducted. JDM has classic, pathognomonic skin manifestations that may or may not correspond with muscle inflammation. To avoid complications, early diagnosis and prompt treatment is the mainstay. NFC acts as an important diagnostic tool and also helps to characterize the phase of disease.